0352 Does the size of a company make a difference to the prevalence of exposure?. (21st August 2017) - Fritschi, Lin; El-Zaemey, Sonia; Darcey, Ellie; Reid, Alison; Rushton, Lesley; McElvenny, Damien
Abstract : About two-thirds of workers in high-income countries work in micro (<5 employees) small (5–20 employees) and medium (20–200 employees) sized companies. Nevertheless, regulatory bodies and many research projects predominantly work with large companies (>200 employees) perhaps because they are more convenient to study. For example, a survey of exposure to silica in the UK undertook 44 site visits, with none of the visits involving sole-trader or micro companies. We undertook a national population-based survey of nearly 5000 Australian workers to examine the occupational prevalence of exposure to 27 asthmagen groups. Seventy percent worked in companies with <200 workers and nearly 20% worked in micro-companies. The overall prevalence of any exposure showed no trend with company size. However, there was considerable variation by agent. For example, flour exposure was most common in medium and small companies, while epoxy and isocyanate exposures were most common in micro companies. The prevalence of exposure was highest in large companies for only 5/27 asthmagen groups and, except for industrial cleaning and sterilising agents, these were relatively rare exposures (medications, ethylene oxide, reactive dyes, and flowers). Our study shows that taking a population-based approach in studies describing exposure is likely to give a better overall picture of where the majority of people are exposed to the hazards. This approach permits the targeting of prevention to the places where we can benefit the greatest number of workers. Nationally-representative studies are needed to ensure that our understanding of occupational exposure is based on evidence, not convenience.